PENGARUH PELAYANAN TERHADAP TINGKAT KEPUASAN KONSUMEN WISATA AGRO PETIK JERUK MALANG - Feliks Aran; Gettik Purwanti; Risca Sari; Sulton Sholehuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Competition in the business world becomes Agro Tourism in the city of Malang to be able to read opportunities and be able to learn the character of consumers so that Agro Petik Jeruk Tourism can still exist. The purpose of this study was to find out how the service affects the level of consumer satisfaction in Citrus Dau Agro Tourism. This research was carried out in Selorejo Village, Dau District, Malang Regency. The data collected are primary and secondary data. Data analysis used quantitative analysis. Sampling was carried out using the Accidental Sampling method (by chance), as many as 78 Malang Agro Petik Jeruk Tourists. This research uses simple linear regression analysis with SPSS program. The results of this study show that from all variables it is known that the responsiveness and empathy variables have a significant effect on consumer satisfaction. While the variables of Direct Evidence, Reliability and Assurance have no significant effect on consumer satisfaction